Development of Teachers’ Guide in Using Reinforcement Strategy for TEYL - Purnamasari, Ni Made Gina; Marhaeni, A. A. I. N.; Artini, L. P. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This study aimed at describing why a teacher’s guide in using positive reinforcement strategy for TEYL needed to be developed, developing a teachers’ guide in using positive reinforcement strategy for TEYL and analyzing the quality of the teacher’ guide. The R&D by Gall, Gall & Borg’s (2003) model was employed in this study, comprising 6 steps, including need analysis, product planning and designing, product developing, product evaluation, revision and final product. The results indicated that first, the teacher’s guide needed to be developed was a teacher’s guide that focused on the aspects of content, presentation, language and illustration and graphics; second, the development of the product was using the analysis of responses from teacher through questionnaires coupled with literature review of the characteristics of a good teacher’s guide, types of positive reinforcement and positive reinforcement strategy and the product was developed into five chapters including praise, symbolic, token, tangible and activity reinforcement chapters; third, the quality of the product met the criteria of a good and excellent product with the score from expert judges were 135, 173 and 174. These findings have important contribution to teacher’s pedagogical and professionalism competence in general or the teacher’s ability to use positive reinforcement strategy in particular.